Comparison between the use of open and walled platforms by juvenile blue foxes (Alopex lagopus) - Korhonen, Hannu; Niemelä, Paavo (Jokioinen : Agricultural Research Centre of Finland, 1996)
Selostus: Näköesteen vaikutus sinikettujen hyllynkäyttöön